Device-Based Measures of Sedentary Time and Physical Activity Are Associated With Physical Fitness and Body Fat Content - Vaara, Jani P.; Vasankari, Tommi; Wyss, Thomas; Pihlainen, Kai; Ojanen, Tommi; Raitanen, Jani; Vähä-Ypyä, Henri; Kyröläinen, Heikki (Frontiers in Sports and Active Living, 2020)
Introduction/Purpose: Physical activity and sedentary time may associate with physical fitness and body composition. Yet, there exists some observational studies that have investigated the associations of device-based measures of sedentary time and physical activity (PA) with cardiorespiratory fitness (CRF) and body composition but associations with muscular fitness (MF) are less studied. Methods: Objective sedentary time and physical activity was measured by a hip worn accelerometer from 415 young adult men (age: mean 26, standard deviation 7 years). Cardiorespiratory fitness (VO2max) (CRF) was determined using a graded cycle ergometer test until exhaustion. Maximal force of lower extremities was measured isometrically and lower body power was assessed using standing long jump (MF). Body composition was determined with bioimpedance method. Single and compositional approach was used in regression analysis. Results: Mean sedentary time was 707 (standard deviation 133) minutes per day (77 ± 8% of the wear time). Volumes of all PA intensities were positively associated with CRF and associations showed linearly increasing magnitudes with higher intensities in single regression models adjusted for age and smoking (p < 0.001). Similarly, PA intensities were positively associated with lower body MF, however, with weaker associations (p < 0.005). After further adjustment for resistance training, the associations remained significant. The associations of the relative distribution of time within sedentary behavior (SB), light intensity PA (LPA) and moderate-to-vigorous PA (MVPA) behaviors as a whole with using compositional analysis further revealed that within the composition MVPA and SB were positively associated with CRF and MF (p < 0.001), while LPA was not. In addition, within the composition, accumulated PA bouts lasting more than 3 min were consistently associated with CRF and MF, and with all body composition variables (p < 0.001), while sedentary time was associated with body fat percentage (p < 0.001). Conclusion: Promoting physical activity and reducing sedentary time may have positive influence on physical fitness and body fat content, and thereby may offer positive health effects. Physical activity of higher intensities may offer greater benefits.